SEA PENS (CNIDARIA: OCTOCORALLIA: PENNATULOIDEA) FROM THE MAR DEL PLATA SUBMARINE CANYON AND OUTSKIRTS - Risaro, Jessica; Lauretta, Daniel (Zootaxa, 2023)
During this work, over 200 specimens of sea pens (Anthozoa: Octocorallia: Pennatuloidea), collected in the Mar del Plata submarine canyon and outskirts (38ºS, up to 3500 m depth) during 2012 and 2013 were analyzed. Of the total, about 160 were identified in seven species of Anthoptilum, Distichoptilum, Kophobelemnon, Pseudumbellula, Solumbellula and Umbellula. Three of those represent new records for the southwestern Atlantic Ocean off Argentina.